Analyzing Determinants of Consumer Purchasing Behavior toward Solar Panels in Indonesia - Dadang Hermawan; Sipah Audiah; Muhammad Faizal Fazri; Ivan Kovac (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2025)
The growing global emphasis on sustainable energy, combined with the relatively slow adoption of solar technology in Indonesia, underscores the necessity of understanding consumer purchasing behavior toward renewable energy products. This study aims to identify and analyze the determinants influencing consumer purchasing behavior toward solar panels in Indonesia using the SmartPLS approach. Data were collected through an online survey targeting individuals who are interested in or have previously purchased solar panels. The SmartPLS method was employed to examine the relationships among key variables, including perceptions of sustainability and environmental benefits, knowledge and information regarding solar panels, economic factors such as price and promotional strategies, and consumer demographic characteristics. The analysis revealed that sustainability perception, knowledge, and economic considerations significantly influence consumers purchase intentions. Furthermore, demographic variables such as age, income, and education were found to shape consumer attitudes and purchasing behavior. These findings offer valuable insights into the behavioral dynamics underlying solar panel adoption in Indonesia and provide practical implications for policymakers and industry stakeholders in designing effective marketing strategies and policy frameworks to accelerate renewable energy adoption nationwide.